Cultural Heritage of the Azerbaijani People as a Basis of Development of Ethnotourism in the Republic - Boyuk Aga Afaq (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The modern economy includes important industry - tourism industry. This industry plays a significant role in the socio-economic development of countries, shaping their image. The author characterized the state program of development of the tourism industry in Azerbaijan, called unique monuments and activities carried out for the tourists in the country. Particular attention is paid to the analysis of ethno-tourism.